Knowledge, Attitude, and Practice about informed consent amongst Resident doctors at Rural Medical Institute of Central India - Shashank Gotarkar1 , Prakash Mohite2 , Kumar Bijyendra Sourabh1 , Alka Rawekar3 (Indian Journal of Forensic Medicine & Toxicology, 2021)
Informed consent is the process by which the treating health-care provider discloses appropriate informationto the patient so that the patient may make a voluntary choice to accept or refuse treatment. There are fewstudies done amongst the medical residents in India about informed consent. The residents are the steppingstone of the Medical profession, it is proposed that the perception about the informed consent amongstthe residents shall be sought. Hence, the study was undertaken with the aim, to appraise the knowledge,attitude, and practices of residents of all three years toward ‘informed consent taking’ with the objectives ofassessing and comparing the knowledge, attitude and practices of obtaining informed consent. The surveyquestionnaire was circulated and data was collated. It was developed in Knowledge, Attitude and practicedomain and analysis was done. Based on the result, it was concluded that, in all three domains, there wasascendency of Knowledge, Attitude and Practice in three years of resident doctors.